Peningkatan Pengetahuan Karyawan Rumah Sakit Umum Daerah Labuang Baji Makassar Pasca Pelatihan Pelayanan Prima - Fridawaty Rivai; Syahrir A. Passinringi; Noer Bahry Noor; Nur Arifah; Adelia U. Ady Mangilep (Faculty of Engineering UNHAS, 2019)
The problem occured in Labuang Baji Makassar Hospital as a newly formed hospital with health workers, especially nurses mostly comes from fresh graduates so their experience and skills of serving patients are still low. From the data that we obtained, complaints against the services of Labuang Baji Makassar Hospital are staff friendliness only reached 24% and slow service with a total of 21%. Quality services are the expectation of all patients who received health service. Even so, not all the hospital able to offer a service that desired. This is because of good quality health services can only be administered by the professional workers who have good knowledge and skills, so the patient can feel comfortable. The excellent service training method was involved the trainee partners. So, this training can be expected to improve the trainee become trainers to train other Labuang Baji Hospital staff. This training will be conducted by applying discourse methods, question and answer, group discussions, games, simulations and group presentation. One group pre-test and post-test was conducted with 16 participants to see the impact from the training, The results show that there awas an increased knowledge of the excellent service participants before the training and after the training. Before the training the level of knowledge of 9 people (56.3%) who were in high level, and after training increased to 93.8% or as many as 15 people. Based on the results of the analysis on excellent service training there was an increased in participants' knowledge about the concept of hospital services, customer satisfaction and loyalty, attitude and appearance of excellent service, verbal and non-verbal communication in health services, intelligence development, transportation assistance, satisfaction assistance. With the existence of excellent service training, it is expected that the training participants can apply the knowledge they have obtained in order to provide satisfying services for patients.